Incredible nature - Marciniak, Kristin (Unbelievable (12 Story Library (Firm)), 2018)
Explores a collection of a strange, natural phenomenon from auroras and crystal caves to moving stones and trees with multicolored bark. Includes a glossary, resources for further information, and color photographs.